Struktur dan Budaya dalam Desain Organisasi : Kajian Literatur Sistematis Menggunakan Metode PRISMA - Munawaroh Munawaroh; Rosy Rostiawaty; Fatmi Fatimah Zahra; Putri Alfitriani (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2025)
Organizational Design is the process of determining the structure, layout, and relationships between parts of an organization to achieve goals and increase efficiency. This process includes planning the organizational structure, division of responsibilities, and how tasks are carried out. Organizational design is dynamic and needs to be adjusted to the development and needs of the organization. Advances in technology and organizational culture play an important role in organizational development. A strong and positive organizational culture can increase employee motivation, engagement, and commitment, which have a positive impact on productivity, efficiency, and innovation. Therefore, the preparation of organizational design is very important in determining the right strategy. A well-designed organizational structure can facilitate the exchange of knowledge, communication between members, and uphold employee moral and professional standards. This study uses a literature study method with the PRISMA approach, using data sources from the ScienceDirect database in the last three years. The results of the study show that strategies in organizations must be formulated and implemented in an organized manner to achieve predetermined goals, while paying attention to the existing organizational culture. A flexible and up-to-date organizational structure allows organizations to adapt more quickly to change. Therefore, organizations need to continue to develop and update their organizational structures to remain relevant and effective in achieving their goals.